DiPiro's pharmacotherapy : a pathophysiologic approach - DiPiro, Joseph T.; Yee, Gary C.; Haines, Stuart T.; Nolin, Thomas D.; Ellingrod, Vicki L.; Posey, L. Michael (New York : McGraw Hill, 2023)
'Although pharmacy education and practice has changed dramatically, the importance of pharmacotherapy knowledge has remained the same. In its 2017 update, ACCP listed in-depth pharmacotherapy knowledge as one of the six competencies necessary to provide CMM in team-based, direct patient care environments. Patient-centered pharmacotherapy knowledge represents 65% of the board certification examination for the Pharmacotherapy Specialty. And Pharmacotherapy (or'Therapeutics' or'Pharmacotherapeutics') is a major part of the Doctor of Pharmacy curriculum, usually a series of courses with the most credit hours. Indeed, it is this in-depth knowledge of pharmacotherapy, combined with the clinical experience gained through postgraduate training in direct patient care practice, that allows the pharmacist to be the'medication therapy expert' on the healthcare team and to proactively address medication-related problems. Pharmacotherapy: A Pathophysiologic Approach remains as relevant today as it was when originally published 35 years ago. The 12th edition provides students, pharmacists, and other health professionals with the core pharmacotherapy knowledge necessary to prevent, identify, and manage disease and medication-related problems'--
Includes bibliographical references and index
Keywords: Chemotherapy; Physiology, Pathological